Enzymatic conversion of milk lactose to prebiotic galacto‐oligosaccharides to produce low lactose yogurt. Issue 4 (29th January 2018) - Raza, Awais; Iqbal, Sanaullah; Ullah, Azmat; Khan, Muhammad Imran; Imran, Muhammad
Abstract: Prebiotic yogurt (PY) with improved galacto‐oligosaccharides (GalOS) was produced through transgalactosylation of lactose followed by physico‐chemical and organoleptic evaluation. The chemical composition of fresh and prebiotic milk was statistically ( p  > .05) similar except for lactose which was reduced from 4.8% in control milk to 1.9% in prebiotic milk. Lactose in PY (1.44 ± 0.01%) was statistically reduced as compared to control yogurt (3.4 ± 0.02%), while other parameters, that is, fat, protein, pH, and acidity were statistically similar. Lactose (60%) was bio‐converted producing 0.9 g GalOS, 0.9 g glucose and 0.55 g galactose per 100 g of PY as determined by assay kits and HPLC. The organoleptic evaluation for color, consistency, and overall acceptability was statistically similar for both yogurts while taste and syneresis were improved in PY due to newly produced monosaccharides and GalOS, respectively. It can be concluded that transgalactosylation of milk lactose improves acceptability of PY and is important for lactose intolerant individuals. Practical applications: Lactose intolerance is a serious issue around the globe and it is highly required to produce low lactose or lactose free dairy products. In the present study, major part of milk lactose has been converted to prebiotic galacto‐oligosaccharides using beta‐galactosidase and the prebiotic milk has been used to produce yogurt with significantly reduced lactose. This process is very much required in dairy industry to produce novel dairy products with reduced lactose.